DAYA TARIK WISATA ALAM RIAM KUWEG DI DESA TAMONG KECAMATAN SIDING KABUPATEN BENGKAYANG - Doni, Radite; Rifanjani, Slamet; Latifah, Siti (JURNAL HUTAN LESTARI, 2021)
This study aims to assess the elements of attraction. This research is expected to be input to the local government as a consideration in the management and development of natural tourism objects. The research was carried out for approximately 3 weeks in Tamong Village, Siding District, Bengkayang Regency. This study used a survey method with interview techniques, sampling was carried out by accidental sampling with predetermined criteria and time periods. The data was processed using the guidelines for the analysis of the operating area of natural tourism objects and attractions (ADO-OTDWA) of the directorate general of PHKA which has been modified according to the scores that have been determined for each criterion. The number of respondents was 31 people. The results of the study, Riam Kuweg area has a good value area attraction (A) to be developed as a natural tourist attraction.Keywords: Tamong Village, Riam Kuweg, Natural Attractions.Â AbstrackPenelitian ini bertujuan untuk menilai unsur daya tarik wisata. Penelitian ini diharapkan dapat menjadi masukkan kepada pemerintah setempat sebagai pertimbangan dalam rangka pengelolaan dan pengembangan objek wisata alam. Penelitian dilaksanakan selama kurang lebih 3 minggu di desa tamong kecamatan siding kabupaten bengkayang. Penelitian ini menggunakan metode survei dengan teknik wawancara, pengambilan sampel dilakukan secara accidental sampling dengan kriteria dan jangka waktu yang telah ditentukan. Data diolah dengan pedoman analisis daerah operasi objek dan daya tarik wisata alam (ADO-OTDWA) direktorat jendral PHKA yang telah dimodifikasi sesuai dengan skor yang telah ditentukan untuk masing-masing kriteria. Jumlah responden sebanyak 31 orang. Hasil penelitian kawasan Riam Kuweg memiliki daya tarik area yang bernilai baik (A) untuk dikembangkan sebagai objek wisata alam.Kata Kunci: Desa Tamong, Riam Kuweg, Daya Tarik Alami.